Post‐fracture Risk Assessment: Target the Centrally Sited Fractures First! A Substudy of NoFRACT. (16th August 2019) - Borgen, Tove T; Bjørnerem, åshild; Solberg, Lene B; Andreasen, Camilla; Brunborg, Cathrine; Stenbro, May‐Britt; Hübschle, Lars M; Froholdt, Anne; Figved, Wender; Apalset, Ellen M; Gjertsen, Jan‐Erik; Basso, Trude; et al.
ABSTRACT: The location of osteoporotic fragility fractures adds crucial information to post‐fracture risk estimation. Triaging patients according to fracture site for secondary fracture prevention can therefore be of interest to prioritize patients considering the high imminent fracture risk. The objectives of this cross‐sectional study were therefore to explore potential differences between central (vertebral, hip, proximal humerus, pelvis) and peripheral (forearm, ankle, other) fractures. This substudy of the Norwegian Capture the Fracture Initiative (NoFRACT) included 495 women and 119 men ≥50 years with fragility fractures. They had bone mineral density (BMD) of the femoral neck, total hip, and lumbar spine assessed using dual‐energy X‐ray absorptiometry (DXA), trabecular bone score (TBS) calculated, concomitantly vertebral fracture assessment (VFA) with semiquantitative grading of vertebral fractures (SQ1–SQ3), and a questionnaire concerning risk factors for fractures was answered. Patients with central fractures exhibited lower BMD of the femoral neck (765 versus 827 mg/cm 2 ), total hip (800 versus 876 mg/cm 2 ), and lumbar spine (1024 versus 1062 mg/cm 2 ); lower mean TBS (1.24 versus 1.28); and a higher proportion of SQ1‐SQ3 fractures (52.0% versus 27.7%), SQ2–SQ3 fractures (36.8% versus 13.4%), and SQ3 fractures (21.5% versus 2.2%) than patients with peripheral fractures (all p  < 0.05). All analyses were adjusted for sex, age, and body mass index (BMI); and the analyses of TBS and SQ1–SQ3 fracture prevalence was additionally adjusted for BMD). In conclusion, patients with central fragility fractures revealed lower femoral neck BMD, lower TBS, and higher prevalence of vertebral fractures on VFA than the patients with peripheral fractures. This suggests that patients with central fragility fractures exhibit more severe deterioration of bone structure, translating into a higher risk of subsequent fragility fractures and therefore they should get the highest priority in secondary fracture prevention, although attention to peripheral fractures should still not be diminished. © 2019 American Society for Bone and Mineral Research. © 2019 The Authors. Journal of Bone and Mineral Research published by American Society for Bone and Mineral Research. Abstract : Fractures at central sites are associated with lower BMD at the femoral neck, total hip, and the site with lowest T ‐score, lower TBS, and higher prevalence of vertebral fractures. BMD = bone mineral density; TBS = trabecular bone score.